Dynamics in the History of Religions between Asia and Europe Encounters, Notions, and Comparative Perspectives - Krech, Volkhard; Steinicke, Marion (Dynamics in the History of Religions, 2011)
The conference volume of the Bochumer Kolleg "Dynamics in the History of Religions between Asia and Europe" outlines the thesis that religion is not a homogeneous cultural phenomenon, but a dense network of diachronically and synchronically differing traditions. ; Readership: All those interested in History of Religion and Religious Studies, Sociology, Cultural Studies and Theology, Asian, Middle East and Islamic Studies.